Multisystem Inflammatory Syndrome In Children:Literature Review - Dominicus Husada (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
The COVID-19 pandemic is yet to be over. Although the number of pediatric patients is relatively small, their clinical manifestations differ from the adult group. Multisystem Inflammatory Syndrome in Children (MIS-C) is one of the most recently discussed clinical manifestations. The clinical features of this case resemble those of Kawasaki disease or toxic shock syndrome with limited diagnostic methods. Patients experience gastrointestinal, mucocutaneous, cardiovascular, hematological, and neurological symptoms. There was also an increase in inflammatory parameters and cardiac disorders, which will also be confirmed by electrophysiological and radiological examinations. Management consists of the administration of immunoglobulins, steroids, and some anti-cytokines. When the patient goes into shock, fluid resuscitation is the mainstay of therapy. Until now, the number of MIS-C patients is relatively small compared to the number of COVID-19 cases, and the number of deaths is very minimal as well.